Towards monuments’ holistic digital documentation: The saint neophytos enkleistriotis case study - Ioannides, Marinos; Ioannidis, Charalabos; Enkleistriotis, Archimadrite Neophytos; Castrillo, David; Chatzigrigoriou, Pavlos; Papageorgiou, Eirini; Leventis, Georgios; Nikolakopoulou, Vasiliki; Athanasiou, Vasilis; Bourexis, Fotis; Soile, Sofia; Verykokou, Styliani; et al. (My University, 2016)
The expansion of the term “monument” to include the surrounding area of the tangible cultural asset, its natural environment as well as the intangible data relating to its existence and use has gradually resulted the formation of the term “cultural landscapes”. “Monument” has evolved into “monumental place” and a “place with its own soul” and nowadays into a “unity” incorporating the multiple and diversified views which regard the one and single object, the cultural asset. In this paper and through the presented case study of Saint Neophytos Enkleistriotis monument, we attempt to move further on, from the view of the “unity” and the interdiscipilinary approach to the “holistic” view, treating the cultural asset as a “whole”; a “whole” which will have been created from the harmonious merge of all the multifaced entities of which it is comprised.
Keywords: 3D model; Geometric documentation; Holistic documentation; Orthoimage; Structure from motion; UAV